Hannah Mary Tabbs and the disembodied torso: a tale of race, sex, and violence in America - Gross, Kali N. (Oxford University Press, 2016)
Prologue -- Handle with care -- The woman found -- To do him bodily harm -- Wavy hair and nearly white skin -- Held for trial -- A most revolting deed -- Epilogue